1991
DOI: 10.1038/eye.1991.129
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and contrast sensitivity in cataract: Summation and inhibition of visual performance

Abstract: SummaryPatients exhibiting uniocular cataract often report an improvement in vision on closing their cataractous eye. Such qualitative evidence suggests the presence of bin ocular inhibition-the converse of binocular summation (that is the normal superior ity of binocular over monocular vision). To quantify the extent of inhibition in cataract, binocular and monocular visual acuity and contrast sensitivity were measured in 28 patients. Twelve patients showed binocular inhibition for visual acuity whilst 11 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
(2 reference statements)
0
18
0
Order By: Relevance
“…It is well known that unilateral cataract may cause binocular inhibition, which has been found to occur in up to 40% of these patients. 12 In addition to visual acuity, the role of contrast and glare disability are other factors to address in the context of cataract surgery and driving. Compared with daytime driving, a significantly larger percentage of drivers (P!.0000) experienced problems while driving in darkness 4 months as well as 5 years after surgery (36% and 43%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that unilateral cataract may cause binocular inhibition, which has been found to occur in up to 40% of these patients. 12 In addition to visual acuity, the role of contrast and glare disability are other factors to address in the context of cataract surgery and driving. Compared with daytime driving, a significantly larger percentage of drivers (P!.0000) experienced problems while driving in darkness 4 months as well as 5 years after surgery (36% and 43%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40] Patients who had surgery in both eyes were significantly more satisfied with their visual function than patients who had surgery in only one eye. 36,41 Another study demonstrated that the cataractous eye interfered with the visual function of the pseudophakic eye, and after second-eye surgery, complaints of visual disability were eliminated.…”
Section: Second-eye Surgerymentioning
confidence: 99%
“…Small studies in cataract patients 7,8,11 found evidence of binocular inhibition in contrast sensitivity and visual acuity. However, other populational studies 12,13 found a high correlation between binocular and the better-seeing eye measures, but differed in their results on the existence of binocular summation and inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Binocular summation and inhibition phenomena have been described for visual acuity and contrast sensitivity. [7][8][9] These phenomena are based on the difference between the values of the better eye and the binocular value, that is, with both eyes open. Summation is present when the binocular value is higher than the better eye value, and inhibition when it is lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation